2009
DOI: 10.1055/s-0029-1218021
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Alkynylation of Aryl and Hetaryl Halides: A Journey from Conventional Palladium Complexes or Salts to Palladium/Carbon

Abstract: Palladium-catalyzed alkynylation of aryl and hetaryl halides has found wide application in the areas of synthetic, heterocyclic, and medicinal chemistry. Attempts to introduce the stable and potentially recyclable palladium/carbon has provided an attractive alternative to the homogeneous palladium catalytic process. The present article provides a personal account of the outcome of the use of conventional palladium catalysts versus palladium/carbon, especially under Sonogashira conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(27 citation statements)
references
References 41 publications
1
26
0
Order By: Relevance
“…In view of the promising in silico results obtained for B through docking studies we planned to synthesize molecules based on A including B. A Pd/C-catalyzed coupling-cyclization strategy leading to the formation of indole ring was used to prepare our target molecules (Scheme 1) (Pal 2009;Layek et al, 2009' Pal et al, 2004. We preferred this strategy as the concerned methodology involved the use of less expensive, stable, easy to handle and recyclable Pd/C which is advantageous over the other Pd-based methodologies.…”
Section: Docking Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In view of the promising in silico results obtained for B through docking studies we planned to synthesize molecules based on A including B. A Pd/C-catalyzed coupling-cyclization strategy leading to the formation of indole ring was used to prepare our target molecules (Scheme 1) (Pal 2009;Layek et al, 2009' Pal et al, 2004. We preferred this strategy as the concerned methodology involved the use of less expensive, stable, easy to handle and recyclable Pd/C which is advantageous over the other Pd-based methodologies.…”
Section: Docking Studiesmentioning
confidence: 99%
“…It is worthy to mention that while chloro group of 3-chloroquinoxalin-2-amines is known to participate in the Pd/C-Cu mediated alkynylation reaction , the chloro group of 4 remained inert in the present reaction perhaps due to the higher reactivity of iodo group of 5 towards the Pd catalyst. Thus, the active Pd(0) species generated in situ (Pal, 2009;Layek et al, 2009;Pal et al, 2004) (Scheme 2) undergoes oxidative addition with 5 rather than 4 to give the organo-Pd(II) species E-1 which on trans organometallation with copper acetylide generated in situ from CuI and 4 affords E-2. The reductive elimination of Pd(0) from E-2 affords the internal alkyne E-3 which subsequently undergoes Cu-mediated intramolecular ring closure to give the desired product 6 via E-4.…”
Section: Docking Studiesmentioning
confidence: 99%
“…A broad range of Pd catalysts have been employed for the synthesis of 2-substituted indoles. As a less expensive catalyst system Pd/C-based catalyst for example Pd/C-CuI-PPh 3 has gained considerable interest for the efficient synthesis of various heterocyclic structures including indoles (Pal et al, 2004;Layek et al, 2009;Alinakhi et al, 2011;Rao et al, 2011). The catalyst Pd/C is stable and easy to handle as well as separable from the product.…”
Section: Introductionmentioning
confidence: 99%
“…was used, as it is well known that an important side reaction, namely the Glaser-type oxidative dimerization of the alkyne moiety, usually occurs in the presence of Cu I [8]. Recently, Pal has shown that during the optimization of the reaction conditions for the Pd/C-mediated synthesis of an isocoumarin, the corresponding phthalide was isolated as the major product when 1,4-dioxane was used as solvent [9]. Thus, with the Pd/CÀPh 3 PÀCuI system and Et 3 N in 1,4-dioxane ( Table 1, Entry 1), the 4-azaphthalide (7Z)-7-benzylidenefuro[3,4-b]pyridin-5(7H)-one (1a) was obtained as the major product and the 5-azaisocoumarin 7-phenyl-5H-pyrano [4,3-b]pyridin-5-one (1b) [7] as the minor product, via a 5-exo-dig and a 6-endo-dig cyclization of the Sonogashira intermediate, respectively.…”
mentioning
confidence: 99%